SYSTEMATIC AND SAMPLING MEDIASTINAL LYMPH NODE DISSECTION OF COMBINED TREATMENT OF NON-SMALL CELLS LUNG CANCER IIIA(N2) STAGE - E. O. Mantsyrev; A. V. Vazhenin; O. A. Gladkov; A. A. Lukin; M. N. Mironchenko; Ya. A. Gnatiuk; S. N. Timofeev (Креативная хирургия и онкология)
This article  provides  results  of  combined modality  treatment of  patients with  stage IIIA(N2) non-small cells lung cancer  with systematic and selective   lymph node  dissection. Elicit that  the  selective    lymph  node  dissection is valid for  patients with  stage IIIA(N2) squamous cell carcinoma and right-sided lung cancer when we provide combined modality treatment using adjuvant radiation therapy. Carrying out that  the systematic  lymph node dissection is extend   disease-free survival and  five-year survival rate  when  we  provide combined modality  treatment for  patients with  stage IIIA(N2) squamous cell carcinoma and left-sided lung cancer.